Coleridge's submerged politics the Ancient mariner and Robinson Crusoe - Keane, Patrick J. (Univ. of Missouri Press, 1994)
Coleridge's Submerged Politics explores Coleridge's response to several crucial issues of the revolutionary and post-revolutionary age: the rise and suppression of English radicalism during the decade of the French Revolution and the tragic questions of slavery and the slave trade. The book consists of two distinct but intimately related sections. Starting with omissions in Coleridge's annotations on Robinson Crusoe, Part I traces his positions on race and slavery, connecting Defoe's novel and the slave-trading of its hero with the spectre-bark of The Ancient Mariner considered by several earlier critics as an abolitionist's allusion to the horrors of a slave ship. Keane discusses the numerous similarities that link these two haunting texts: their intertwined motifs of sea, sin, and existential solitude, of transgression, punishment, and at least partial redemption